1993
DOI: 10.1002/jso.2930530505
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptor mRNA in tumorous and non-tumorous liver tissue as detected by in situ hybridization

Abstract: Estrogen receptor mRNA was detected by a non-radioactive in situ hybridization assay in tumor and non-neoplastic liver tissues. A synthetic oligonucleotide complementary to the human estrogen receptor mRNA was 3'-labeled with digoxigenin-deoxyuridine triphosphate (dUTP). Hybrids were revealed by an alkaline phosphatase-conjugated anti-digoxigenin antibody. Fourteen primary hepatocellular carcinoma tissues (and one metastatic) were obtained at surgery from 15 patients. The corresponding nonneoplastic liver tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The low serum levels of LDL-cholesterol in this patient could be related to the decreased synthesis of its precursor VLDL, given the well-known action of oestrogen in stimulating VLDL triglyceride production (141) and the presence of ERs in the liver (142). The very low concentration of HDLcholesterol in the oestrogen-resistant man could be the result of the unopposed action of androgen, which is considered the most important determinant of differences between males and females in serum HDLcholesterol (143)(144)(145)(146).…”
Section: Journal Of Endocrinology (1999) 140mentioning
confidence: 88%
“…The low serum levels of LDL-cholesterol in this patient could be related to the decreased synthesis of its precursor VLDL, given the well-known action of oestrogen in stimulating VLDL triglyceride production (141) and the presence of ERs in the liver (142). The very low concentration of HDLcholesterol in the oestrogen-resistant man could be the result of the unopposed action of androgen, which is considered the most important determinant of differences between males and females in serum HDLcholesterol (143)(144)(145)(146).…”
Section: Journal Of Endocrinology (1999) 140mentioning
confidence: 88%
“…The data, therefore, suggest constitutive expression of the enzyme in the gastrointestinal tract, and that 17HSD type 2 expression is not related to the concentration or type of sex steroid in the blood circulation. However, estrogen receptors, but not androgen receptors, have been localized in many of the cell types of the gastrointestinal and urinary tracts expressing 17HSD type 2 (Riuzeweld de Winter et al 1991, Pacchioni et al 1993, Thomas et al 1993, and additional studies are needed in order to characterize the role of 17HSD type 2 in the regulation of sex steroid action locally in the different cell types of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports on direct detection of ER using specific antibodies. Table 1 gives the details of these studies [32,[39][40][41][42][43][44][45][46][47] . However, all these studies have employed either immunohistochemistry (IHC) or enzyme-immuno assays (EIA) using antibodies specific for only ERα isoform.…”
Section: Estrogen Receptormentioning
confidence: 99%
“…Table 2 gives the details of these studies [18,19,40,45,51,52] . In situ hybridization using ER specific oligonucleotide sequence probe revealed that 11 out of 15 HCC tissue samples expressed ER mRNA [40] . Interestingly, the same samples were found to be negative for ER protein by IHC, suggesting the use of more sensitive methods and more specific antibodies for detecting ER at protein level.…”
Section: Estrogen Receptormentioning
confidence: 99%
See 1 more Smart Citation